(untitled) (American Journal of Islam and Society, 2002)
Many scholars have attempted to tackle the question of why democracy has seemingly failed to take root in the Islamic milieu, in general, and the pre dominantly Arab Middle East, in particular, while the rest of the world has witnessed the fall of"pax-authoritaria" especially in the wake of the demercratic revolution triggered by the failure of communism. Some view this resistance to the Third Wave, as being rooted in the Islamic cultural dynamics of the region, whereas others will ascribe it to the level of political development (or the lack thereof). An anthology of essays, Challenges to Democracy in the Middle East furnishes the reader with five historical case studies that seek to explain the arrested socio politico-economic development of Syria, Lebanon, Iraq, Iran, and Turkey, and the resulting undemercratic political culture that domjnates the overall political landscape of the Middle East. The first composition in this omnibus is "The Crisis of Democracy in Twentieth Century Syria and Lebanon," authored by Bill Harris, senior lecturer of political studies at the University of Otago in Dunedin, New Zealand. Haris compares and contrasts the political development of Syria and Lebanon during the French mandate period and under the various regimes since then. He examines how the two competing forms of nationalism, i.e., Lebanonism and Arabism, along with sectarianism, are the main factors that have contributed to the consolidation of one-party rule in Syria, and the I 6-year internecine conflict in Lebanon. After a brief overview of the early history of both countries, the author spends a great deal oftime discussing the relatively more recent political developments: Syria from 1970 onwards, and Lebanon from I 975 to the I 990s. Harris expresses deep pessimism regarding the future of democratic politics in both countries, which in his opinion is largely due to the deep sectarian cleavages in both states. The next treatise is "Re-inventing Nationalism in B????thi Iraq 1968- 1994: SupraTerritorial Identities and What Lies Below," by Amatzia Baram, professor of Middle East History at the University of Haifa. Baram surveys the Ba·th’s second stint in power (1968-present) in lraq. Baram’s opinion is that a shift has occurred in B????thist ideology from an integrative Pan-Arab program to an Iraqi-centered Arab nationalism. She attributes this to Saddam’s romance with the past, on the one hand, which is the reason for the incorporation of themes from both the ancient Mesopotamian civilization and the medieval Abbasid caliphal era, and, on the other hand, to Islam and tribalism, that inform the pragmatic concerns of the Ba’thist ideological configuration ...